Structure of Male Reproductive System in Spirula (Cephalopoda: Spirula spirula) - R.M. Sabirov; A.A. Novikov; A.V. Golikov (Учёные записки Казанского университета: Серия Естественные науки)
This paper provides a description of general morphology of the reproductive system in male specimens of Spirula spirula, including morphometric characters of spermatophores and features of their production during the ontogenesis. The reproductive system fitted the general scheme of Coleoidea. However, the position of the reproductive system in the body of the studied male specimens was uncommon for all known Cephalopoda: the testis and spermatophoric complex (SC) were located posteriorly into the mantle cavity to the right and to the left from the middle body line, respectively. This symmetric lateral location can be attributed to the development of the internal spiral shell. To connect the testis and SC, an extremely elongated coelomoduct (reproductive funnel) developed. It runs through the empty cavity inside the first (internal) whorl of the shell. Spermatophores were morphologically characterized by the distinguishing structure of their cement body. Spermatophore length was 10.81–12.07 mm, mean length was 11.37 mm, which was 29.2% of mantle length (ML). The quantity of sperm packed in the seminal reservoirs of spermatophores continuously decreased during the ontogenesis. Spermatophore number in the spermatophoric sac was 84, total volume of sperm packed in all spermatophores was 0.0168 cm3, mean mass of the spermatophore was 0.65 mg, total mass of all spermatophores in the spermatophoric sac was 0.021 g. In general, the reproductive system in male specimens of Spirula bears the signs of high specialization (unique topography, elongated coelomoduct, continuous decreasing spermatophorogenesis), which developed during the evolution of ratio of their endogastric shell and visceral inner sac.